Combined experimental and theoretical studies of conformationally diverse (thio)semicarbazone-based semiconducting materials. Issue 14 (21st March 2023) - Panja, Anangamohan; Das, Mainak; Jana, Narayan Ch.; Brandão, Paula; Gomila, Rosa M.; Ortega-Castro, Joaquín; Frontera, Antonio; Ray, Partha Pratim
Abstract : The importance of non-covalent interactions on the stability of conformationally diverse (thio)semicarbazone-based semiconducting materials is investigated. Abstract : This study reports the synthesis and characterization of two closely related semicarbazone/thiosemicarbazone-based organic compounds: N -(2-hydroxy-3-methoxy-5-methylbenzylidene)semicarbazide (1 ) and N -(2-hydroxy-3-methoxy-5-methylbenzylidene)thiosemicarbazide (2 ). Structural studies revealed the conformational diversity in these systems as compound 1 crystallized as only one conformer, while compound 2 crystallized as a mixture of two conformers. DFT calculations in combination with the quantum theory of atoms in molecules (QTAIM) and natural bond orbital (NBO) analyses revealed that the energy difference between the two conformers was larger in compound 1, while the difference between both conformers was very small in the thiosemicarbazide derivative (2 ), in line with the X-ray crystallographic characterizations. The synthesized compounds were tested for their electrical conductivity behaviour via current density–voltage measurements, as well as impedance spectroscopy, which revealed that both compounds were semiconducting in nature, arising from the charge transport through space via π⋯π contacts, and could be useful for the fabrication of electrical devices, particularly 1, in which the conductivity fell by a higher order of magnitude than observed in similar organic semiconductors tested earlier. Moreover, the combined experimental and theoretical studies showed the importance of the non-covalent interactions on the stability of the different conformers, thereby guiding the possible isolations of different polymorphic forms of such conformationally diverse semicarbazone/thiosemicarbazone systems through the selective stabilization of a particular conformer by varying the reaction conditions.